Influence of Tool Finishing on the Wear Development in Strip Drawing Tests with High Strength Steels - Yutian Wu (Japanese Society of Tribologists, 2020)
With the increasing usage of high-strength steel, tool wear becomes a major challenge in sheet metal forming. As tribological properties are in consequence of the system characteristics, wear prediction is extremely difficult. The wear resistance characteristic curve is introduced in a former publication of the authors to predict wear in sheet metal forming. With the help of this curve, the evaluation of the tool life spans in strip drawing tests under different contact pressures is possible. However, other influencing factors on tool wear should also be taken into account. In this paper, two types of tools made from cold working steel and cast iron are used to investigate the influence of the tool characteristics hardness and surface roughness on the wear behavior and the life span in strip drawing tests with high strength steels. Moreover, the dominating wear mechanisms with respect to different tool properties are also discussed. As a consequence, the wear resistance characteristic curves are derived and new values to characterize the wear resistance in terms of hardness and surface roughness are presented. With the results, more knowledge about the influencing factors on wear is given and the life spans of different tribological systems can be quantitatively predicted. Finally, the wear behavior of the tools after rework is also discussed.